Allergome-wide peptide microarrays enable epitope deconvolution in allergen-specific immunotherapy - Mikus, Maria; Zandian, Arash; Sjöberg, Ronald; Hamsten, Carl; Forsström, Björn; Andersson, Morgan; Greiff, Lennart; Uhlén, Mathias; Levin, Mattias; Nilsson, Peter; van Hage, Marianne; Ohlin, Mats (Journal of allergy and clinical immunology, 2021)
The interaction of allergens and allergen-specific IgE initiates the allergic cascade after crosslinking of receptors on effector cells. Antibodies of other isotypes may modulate such a reaction. Receptor crosslinking requires binding of antibodies to multiple epitopes on the allergen. Limited information is available on the complexity of the epitope structure of most allergens. We sought to allow description of the complexity of IgE, IgG4, and IgG epitope recognition at a global, allergome-wide level during allergen-specific immunotherapy (AIT). We generated an allergome-wide microarray comprising 731 allergens in the form of more than 172,000 overlapping 16-mer peptides. Allergen recognition by IgE, IgG4, and IgG was examined in serum samples collected from subjects undergoing AIT against pollen allergy. Extensive induction of linear peptide-specific Phl p 1– and Bet v 1–specific humoral immunity was demonstrated in subjects undergoing a 3-year-long AIT against grass and birch pollen allergy, respectively. Epitope profiles differed between subjects but were largely established already after 1 year of AIT, suggesting that dominant allergen-specific antibody clones remained as important contributors to humoral immunity following their initial establishment during the early phase of AIT. Complex, subject-specific patterns of allergen isoform and group cross-reactivities in the repertoires were observed, patterns that may indicate different levels of protection against different allergen sources. The study highlights the complexity and subject-specific nature of allergen epitopes recognized following AIT. We envisage that epitope deconvolution will be an important aspect of future efforts to describe and analyze the outcomes of AIT in a personalized manner.